Consumerism Value Through Artwork Production By Malaysian Artist - Saat, Mohammad Khizal; Shaari, Shahrul Anuar (2016)

(untitled)
The purpose of this writing is to further discuss the values of consumerism through the exploration of images, texts, and materials via the production of artwork by a few artists in Malaysia. The lifestyle of the society is influenced by the institutional social culture which is upheld by the surrounding environment. The value of consumerism can be indentified from the way of lifestyle projected from the society which effected and contribute to form of behaviours and expression of today ‘s society and eventually will produce as symbols and belief among social community.This includes artists who views this issue as part of their research theme. Through the application in artwork production, the understanding towards the concept of materialsm and consumerism agenda in society could be manifest, translated and arranged in various forms. The translation of consumerism values is put forward by giving an interpretation on how a social environment which currently exists is severely impacted by the elements of consumerism and brings various conotations on to the lifestyle as well as to the belief of the current society.